PIGEON PEA PROTEIN CONCENTRATE (CAJANUS CAJAN) SEEDS GROWN IN ECUADOR FUNCTIONAL PROPERTIES - A, PAZMIÑO; G, VÃsquez; W, Carrillo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to obtain pigeon pea protein concentrate (PC) of green seeds and mature seeds from Cajanus cajan grown in Ecuador and evaluate their functional properties. Methods: Pigeon PC of green seeds (GPPPC) and pigeon PC of mature seeds (MPPPC) were obtained by alkaline extraction (pH 8.5) using the isoelectric precipitation at pH 4.5 method. Content of protein was determined using the Dumas method. Functional properties were evaluated with the following functional properties: Protein solubility (PS), water absorption capacity (WAC), oil absorption capacity (OAC), emulsifying activity index (EAI), emulsion stability index (ESI), foaming capacity (FC), and foam stability (FS). Results: GPPPC and MPPPC are statistical different (p<0.05) in the evaluation of functional properties such as WAC, OAC, EAI, ESI, FC, and FS. GPPPC and MPPPC have different PS profiles. GPPPC is higher in WAC and EAI; MPPPC is higher in OAC, EAI, FC, and FS properties. Conclusions: PPPC can be used as functional ingredients that provide technological improvements in the generation of new food products. Both seed, green or mature, can be considered to obtain PPPC. The green or mature PPPC to be used would depend on the technological property required in the specific process for the food industry.